The influence of independence, integrity, professionalism, and objectivity on fraud prevention in auditors with auditor ethics as a moderating variable: Empirical study at the Representative Office of the Supreme Audit Agency in North Sulawesi Province - Sinaga, Indra Rolando; Sondakh, Jullie J; Warongan, Jessy D. L (The Contrarian : Finance, Accounting, and Business Research, 2024)
This study aims to analyse the influence of independence, integrity, professionalism, objectivity, and ethics on fraud prevention among auditors. Additionally, this study also treats the auditor's ethics as a moderating variable. Conducted through survey methodology, the study involved distributing questionnaires to all auditors in the Audit Board of the Republic of Indonesia (or BPK) Regional Office for North Sulawesi Province. The questionnaires were disseminated to 138 respondents and achieving for 100% response rate. Analytical methods employed encompassed multiple moderated regression analysis. The results indicate that independence, integrity, professionalism, objectivity, and ethics positively influence fraud prevention. Moreover, the results also reveal that the auditor's ethics can moderate the influence of independence and professionalism on fraud prevention. The implications of the findings suggest that higher levels of independence, integrity, professionalism, objectivity, and ethics tend to increase effectiveness in fraud prevention within the BPK Regional Office for North Sulawesi Province.